Reducing sovereign debt levels in the post-Covid Eurozone with a simple deficit rule - Thomas Jost; Karl-Heinz Tödter (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2021)
Debt levels in the eurozone have reached new record highs. The member countries have tried to cushion the economic consequences of the corona pandemic with a massive increase in government spending. There are various calls to abolish or soften the Maastricht rules of limiting sovereign debt. The authors see the risk of a new sovereign debt crisis in this decade if it is not possible to bring public debt down to an acceptable level. The authors propose a new fiscal rule that would be suitable and appropriate for this purpose. In contrast to the rigid 3% Maastricht-criterion, the rule is flexible and it addresses the main problem: excessively high public debt ratios. The authors argue that it lowers the existing incentives for highly indebted governments to exert expansionary pressure on monetary policy. If obeyed strictly, the rule reinforces the snowball effect and reduces the excessively high debt ratios within a manageable period, even if nominal growth is weak. This is confirmed by simulations with different scenarios as well as with the hypothetical application of the new fiscal rule to eurozone economies from 2022 to 2026. Finally, the authors take up the proposal by ESM economists to increase the permissible debt ratio from 60 to 100% of GDP in the eurozone. – – Die Verschuldung in der Eurozone hat neue Rekordhöhen erreicht. Die Mitgliedsländer haben versucht, die wirtschaftlichen Folgen der Corona-Pandemie durch eine massive Erhöhung der Staatsausgaben abzufedern. Es gibt verschiedene Forderungen, die Maastricht-Regeln zur Begrenzung der Staatsverschuldung abzuschaffen oder aufzuweichen. Die Autoren sehen die Gefahr einer neuen Staatsschuldenkrise in diesem Jahrzehnt, wenn es nicht gelingt, die Staatsverschuldung auf ein akzeptables Niveau zu senken. Die Autoren präsentieren eine neue flexible Fiskalregel. Damit sollen die hohen Schuldenquoten sinken. Bei strikter Befolgung soll die Regel die hohen Schuldenquoten innerhalb eines überschaubaren Zeitraums reduzieren, selbst wenn das nominale Wachstum schwach ist. Das wird durch Simulationen mit verschiedenen Szenarien sowie durch die hypothetische Anwendung der neuen Fiskalregel auf die Volkswirtschaften der Eurozone von 2022 bis 2026 bestätigt. Schließlich greifen die Autoren den Vorschlag von ESM-Ökonomen auf, die zulässige Schuldenquote in der Eurozone von 60 auf 100 % des BIP zu erhöhen.
Keywords: H62; H68; F55; F45; 330; Eurozone; fiscal rules; Maastricht criteria; sovereign debt; Stability and Growth Pact